2018
DOI: 10.1155/2018/9390810
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidin Extract Prevents Ovarian Aging by Inhibiting Oxidative Stress in the Hens

Abstract: Oxidative stress is an important inducement in ovarian aging which results in fecundity decline in human and diverse animals. As a potent antioxidant, grape seed proanthocyanidin extract (GSPE) was investigated to ameliorate chicken ovarian aging in this study. Firstly, ovarian antioxidant capacity of hens at different ages (90, 150, 280, and 580 days old) was compared to elucidate its age-related changes. Subsequently, a D-gal-induced (2.5 mg/mL) aging ovarian model was established and the cultured ovarian ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 52 publications
(54 reference statements)
2
107
0
Order By: Relevance
“…In broiler chickens, GSE dietary supplementation has been demonstrated to be an immunostimulant agent [27,28] and to improve fatty acid profile in liver [29]. In hens, it was also able to modulate egg quality and composition and laying performance [30,31], (supplementation for 5 weeks) and to prevent the ovarian aging process [32]. However, the effects of chronic GSE dietary supplementation on oxidative stress, growth performance and metabolic parameters including plasma adipokines have never been investigated in hens.…”
Section: Introductionmentioning
confidence: 99%
“…In broiler chickens, GSE dietary supplementation has been demonstrated to be an immunostimulant agent [27,28] and to improve fatty acid profile in liver [29]. In hens, it was also able to modulate egg quality and composition and laying performance [30,31], (supplementation for 5 weeks) and to prevent the ovarian aging process [32]. However, the effects of chronic GSE dietary supplementation on oxidative stress, growth performance and metabolic parameters including plasma adipokines have never been investigated in hens.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other studies have demonstrated that oxidative stress is associated with granulosa cell dysfunction and apoptosis and in an age-related decline in female fertility [ 15 , 16 ]. As in mammals, hens also undergo severe decreases in fecundity due to the increase in ovarian oxidative stress during the aging process [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many natural plant extracts such as resveratrol [ 26 ], hesperidin [ 27 ] and grape seed proanthocyanidin extract [ 17 ] have been applied towards reducing oxidative stress in the ovaries in order to maintain normal function. Lycopene is a kind of carotenoid compound that exists in tomatoes, watermelon, pink grapefruit, guava and other red fruit [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that GSPE could rescue the antioxidant capacity decline by increasing the antioxidase activities and their gene expression in either D-gal-induced or natural aging ovaries. 42 Moreover, GSPE could maintain the homeostasis between cell proliferation and apoptosis in the D-gal-induced and natural aging ovaries, as well as alleviate D-gal-induced nucleus chromatin condensation in the ovarian granulosa cells. In conclusion, GSPE treatment can effectively prevent the ovarian aging process in hens by reducing oxidative stress 42 which will help to maintain the sexual health of females at later age of their life.…”
Section: Grape Seed Extractmentioning
confidence: 99%